A importância da matemática para o estudo dos buracos negros - DANTAS, Ingrid Cristina Leão (2024)
When we talk about Black Holes, the image of a “void” in the middle of space that sucks everything around it usually comes to mind, some people even create theories about space-time travel. Bearing in mind that all the knowledge we currently have about black holes, despite not knowing much about them, is thanks to mathematics. The present work deals with the importance of mathematics in the study of black holes, in order to show how its involvement was vital so that what is known today about them could be known. Therefore, it was necessary to show its participation since theorization in the 20th century, until the image registration obtained in recent years, the greatest proof we have of its existence so far. Thus, a qualitative bibliographic research was carried out, where data were collected through research in books, articles and other works published on the subject to validate its reliability. In view of this, it was verified that mathematics was present in all processes involving these objects, where it was possible to conclude that if it were not for mathematics, we would not even know of their existence.